2018
DOI: 10.15761/brcp.1000173
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment for indeterminate pulmonary nodules using a novel, plasma-protein based biomarker assay

Abstract: Background: The increase in lung cancer screening is intensifying the need for a noninvasive test to characterize the many indeterminate pulmonary nodules (IPN) discovered. Correctly identifying non-cancerous nodules is needed to reduce overdiagnosis and overtreatment. Alternatively, early identification of malignant nodules may represent a potentially curable form of lung cancer. Objective: To develop and validate a plasma-based multiplexed protein assay for classifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Biomarker candidates for which sensitive and specific assays could be developed to measure subtle changes in circulating levels associated with the presence of lung cancer where advanced through the assay development and characterization process. We evaluated the customized assays in early discovery work to measure the biomarker levels in a cohort of subjects from an observational study of PET-CT imaging for lung cancer [ 15 ]. Those studies identified that the plasma levels of EGFR, ProSB, and TIMP1 in current smokers were the most informative in assessing the likelihood of malignancy in subjects with an indeterminate lung nodule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomarker candidates for which sensitive and specific assays could be developed to measure subtle changes in circulating levels associated with the presence of lung cancer where advanced through the assay development and characterization process. We evaluated the customized assays in early discovery work to measure the biomarker levels in a cohort of subjects from an observational study of PET-CT imaging for lung cancer [ 15 ]. Those studies identified that the plasma levels of EGFR, ProSB, and TIMP1 in current smokers were the most informative in assessing the likelihood of malignancy in subjects with an indeterminate lung nodule.…”
Section: Discussionmentioning
confidence: 99%
“…The SVM model output is a score from 0 to 100% that indicates the probability of malignancy for the nodule. A cutoff value of 50% was identified from earlier training and validation studies as the optimal separation between nodules at lower risk from those at higher risk of being malignant [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The biomarker algorithmbased test correctly identified 44 (65%) of these intermediate-risk samples as lower risk (n = 16) or higher risk (n = 28). The test showed a sensitivity of 94% and a negative predictive value (NPV) of 94% [8] in the intended use population having a cancer prevalence rate of 25% [10]. Almost all subjects (98%) had early stage disease as defined by lung cancer Stage I or II [8].…”
Section: Introductionmentioning
confidence: 98%
“…A recent publication highlights the clinical validation and performance of a novel, multiplexed, plasma protein signature as a risk assessment tool [8]. The authors established the assay's ability to aid in correctly identifying the risk of malignancy for a pulmonary nodule that falls into the inconclusive intermediate risk for lung cancer as calculated by the VA Clinical Factors Model [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation